ANALISIS SOAL UAS SEJARAH PEMINATAN KELAS XI IPS SMAN 3 KETAPANG TAHUN AJARAN 2018/2019 - Tri Riski Maulia; Sri Buwono; Ika Rahmatika Chalimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research is to find out the quality of items and the quality of the final exam test in the last semester of historical subject classes XI IPS at SMAN 3 Ketapang School Year 2018/2019. The research method used is a descriptive method with a quantitative approach. The research data was about test items and the students answer sheet. The anaylisis used Iteman version 3.00 and Microsoft Excel 2010. The research results for the discrimination index of multiple choice are 40 items (89%) is acceptable and 5 items (11%) rejected. As for essay 4 items (80%) is acceptable and 1 item (20%) the discrimination index is rejected. The difficulty index of multiple choice are 3 items (6.7%) is hard, 23 items (51.1%) is medium, and 19 items (42.2%) is easy. As for the essay 5 items (100%) is hard. The spieler effectiveness are 12 items (27%) must be revised the deceptions and 33 items (73%) the deceptions is not revised. Item validity of multiple choice are 40 items (89%) valid and 5 items (20%) invalid. Content validity of the multiple choice are 5 items (11%) and 1 essay item (20%) revised or replaced. The reliability index of multiple choice test is 0.771 which means reliable. While the essay is in the number 0.09 which means it is not reliable. Keywords: Final Examination, Historical Subject, Item Analysis.